Evaluating The Validity And Reliability Of A Transcultural Nursing - Based Specific And Sensitive Nutritional Intervention Questionnaire To Address Stunting - Wiastuti, Siti Marina; Susanto, Tantut; Rahmawati, Iis (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Stunting is a global health issue caused by chronic malnutrition that significantly impacts children's growth and development. Jember Regency has the highest stunting prevalence in East Java, reaching 34.9%, thus requiring effective solutions. Specific and sensitive nutritional interventions based on transcultural nursing are seen as crucial efforts in reducing stunting rates. However, a valid and reliable instrument is needed to assess the effectiveness of interventions at the family level. This study aims to develop and validate a specific and sensitive nutritional intervention questionnaire based on transcultural nursing as a tool to measure family awareness in preventing stunting in Jember Regency. This research involved 42 mothers of stunted children as respondents, residing within the working area of the Rambipuji Public Health Center. The instrument's validity was assessed using the Content Validity Index (CVI), while reliability was measured through Cronbach's alpha coefficient to ensure consistency. The questionnaire includes nine dimensions, such as Technology, Religion and Life Philosophy, Social and Family Support, Cultural Values and Lifestyle, Specific and Sensitive Nutritional Interventions. Content validity ranged from 0.80 to 1.00, and internal consistency measured by Cronbach's alpha showed values between 0.752 and 0.950. These results indicate that the questionnaire is effective in measuring family awareness and the effectiveness of nutritional interventions. This questionnaire is a valid and reliable instrument to support the optimization of sustainable stunting prevention programs in Jember Regency.